Melatonin Promotes Cheliped Regeneration, Digestive Enzyme Function, and Immunity Following Autotomy in the Chinese Mitten Crab, Eriocheir sinensis - Zhang, Cong; Yang, Xiao-zhen; Xu, Min-jie; Huang, Gen-yong; Zhang, Qian; Cheng, Yong-xu; He, Long; Ren, Hong-yu (Frontiers in Physiology, 2018)
In the pond culture of juvenile Eriocheir sinensis, a high limb-impairment rate seriously affects the culture success. Therefore, it is particularly important to artificially promote limb regeneration. This study evaluated the effects of melatonin on cheliped regeneration, digestive ability, and immunity, as well as its relationship with the eyestalk. It was found that the injection of melatonin significantly increased the limb regeneration rate compared with the saline group (P < 0.05). The qRT-PCR results of growth-related genes showed that the level of EcR-mRNA (ecdysteroid receptor) and Chi-mRNA (chitinase) expression was significantly increased following the melatonin injection, while the expression of MIH-mRNA (molt-inhibiting hormone) was significantly decreased (P < 0.05). Melatonin significantly increased lipase activity (P < 0.05). We observed that the survival rates of limb-impaired and unilateral eyestalk-ablated crabs were substantially improved following melatonin treatment, whereas the survival of the unilateral eyestalk-ablated crabs was significantly decreased compared with the control group (P < 0.05). Furthermore, the results of serum immune and antioxidant capacity revealed that melatonin significantly increased the total hemocyte counts (THC), hemocyanin content, total antioxidant capacity (T-AOC), acid phosphatase (ACP), and glutathione peroxidase activity (GSH-Px), whereas the immune-related parameters were significantly decreased in eyestalk-ablated crabs (P < 0.05). Therefore, these findings indicate that melatonin exerts a protective effect on organism injury, which could promote limb regeneration by up-regulating the expression of growth-related genes, improve digestive enzyme activity, and strengthen the immune response, particularly antioxidant capacity.